2017
DOI: 10.1111/1462-2920.13638
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in freshwater picocyanobacteria

Abstract: Picocyanobacteria can occur as single-cell (Pcy) or as colonies (CPcy). Published evidence suggests that some Pcy strains have the capability to aggregate under certain culture conditions, however this has not been demonstrated to occur in natural environments. We investigated whether the Pcy and CPcy belong to the same species (i.e. phylotype), and the factors that determine their morphological and genetic variability in a hypertrophic shallow lake dominated by picocyanobacteria. Six main different morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…The separation of Anathece from Cyanobium was based on morphology (Komárek et al, 2011), whereas there is no evidence for this in the phylogeny. Moreover, Huber et al (2017) demonstrated the variability of this feature. The strains that we isolated belonged to the same Cyanobium lineages, but consisted of solitary cells under our grazer-free culture conditions.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The separation of Anathece from Cyanobium was based on morphology (Komárek et al, 2011), whereas there is no evidence for this in the phylogeny. Moreover, Huber et al (2017) demonstrated the variability of this feature. The strains that we isolated belonged to the same Cyanobium lineages, but consisted of solitary cells under our grazer-free culture conditions.…”
Section: Discussionmentioning
confidence: 90%
“…The position of the thylakoids cannot be determined with light microscopy, so the only remaining easily visible difference is the formation of colonies. For example, Jezberová and Komárková (2007a,b) and Huber et al (2017) demonstrated the variability of this feature under different culture conditions. The formation of colonies depended on the presence of a grazer.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations